CHARACTERIZATION AND BIOSYNTHESIS OF SCL-CO-MCL BY BACILLUS SP.OU35 - P.NAGAMANI; SK.MAHMOOD (International Journal of Pharma and Bio Sciences, 2012)
This study aimed to describe an aerobic, gram positive, mesophilic and heterotrophic bacterium, designated OU35 isolated from polluted pond. In shake flask experiments, this bacterium produced a novel scl co mcl PHA, composed of 3-hydroxy butyrate (95 %), 3-hydroxy octanoate (2.5%), and 3-hydroxy decanoate (2.5%), from glucose and rice bran as carbon sources. The yield of the PHA was 1.217g/l and1.530 g/l respectively. Optimal growth occured between 28 and 37oC, at a PH between 6.0 and 7.8 and at an ionic strength of 12gl-1 of sea salts. The G+C content of DNA is 45.25%. Major fatty acids were iso-C15, 0(20.29%), anteiso-C15, 0(5.31%), iso-C16, 0(8.35%), anteiso-C15,0(5.31%), iso-C16,0(8.35%). Strain exhibited maximum homology of 96.28% to Bacillus aryabhattai B8W22T, 95.97% to B.megaterium IAM 13418T, and 95.282% to B. flexus IFO15715T by 16S rDNA sequencing. The 16S rRNA gene sequence is deposited in EMBL/Genbank with accession number FN663629 and has been deposited in the CCTCC as strain CCTCC AB2011468T